Evaluación de la calidad de leche en centros de acopio del cantón Chone - Zambrano Cedeño, Elian Gregorio (2025)
The study aimed to evaluate the quality of raw milk in three collection centers in the Convento parish, Chone canton, considering hygienic and safety parameters. A non-experimental, descriptive design with a qualitative approach was applied, collecting 102 samples from centers A, B, and C, which were subjected to physicochemical analyses, somatic cell counts, and detection of antibiotic residues. Protein, lactose, non-fat solids, water addition, and reception temperature were analyzed, as well as the presence of beta-lactams, tetracyclines, and sulfonamides. Most samples partially complied with NTE INEN 9:2012, although deficiencies were identified, such as protein below 3.1%, low non-fat solids in one center, reduced lactose, water addition in all collection centers, and temperatures above 8 °C. Somatic cell counts showed significant differences, with some cases exceeding 500,000 cells/mL, indicating possible subclinical mastitis and hygiene deficiencies. Beta-lactams were detected in low proportions, while tetracyclines and sulfonamides were not found. These findings reflect shortcomings in the quality, hygiene, and safety of milk, associated with inadequate milking and storage practices. It is recommended to reinforce the cold chain, implement mastitis prevention programs, and strictly comply with drug withdrawal periods, thereby ensuring a safe product in accordance with national regulations.